Development of Interactive Student Worksheets Based on Worksheets as Student Learning Media - Abdurrahman Badri (Yayasan Siti Widhatul Faeha Salahudin Syawal, 2025)
This research is a developmental study focused on creating interactive Student Worksheets utilising Liveworksheet as a pedagogical aid for learners. The employed development paradigm is the 4D model by Thiagarajaran (1974), comprising four stages: define, design, develop, and disseminate. This study used a learning media validation sheet and a readability questionnaire for students as its tools. The interactive LKPD product received validation from three experts: a material expert, a media expert, and a biology teacher from SMA NW Lendang Kekah. The readability of the interactive Student worksheets was evaluated on Grade X students throughout the deployment phase. According to the research findings, the material expert assigned a score of 72%, signifying the product's suitability; the media expert assigned a score of 97%, denoting the product's high suitability; and the biology instructor assigned a score of 95%, showing the product's high suitability. The readability assessment yielded a score of 82%, signifying the product's good suitability. This study concludes that the interactive Student worksheets with Liveworksheet are exceptionally effective as a learning aid to enhance the educational process.